Antropologi di Persimpangan Jalan: Refleksi dari Pemahaman akan Tindakan Kaum Muda - Irwan Abdullah (Antropologi Indonesia, 1997)
Irwan Abdullah presents his argument that the concept of deviant is no longer relevant to the analysis of the activities of young people's. An effort to understand their activities as a subordinate expression of the culture domination is appropriate. Perceiving their activities as deviant cannot be understood with Geertz's cultural concepts. He said that culture is shared values. Young people have their own way in understanding the meaning of life. Their values are not merely inherited from older generation, but the products of the reinterpretation process. The author further argues that in today's social transformation process and media becomes the great agent in disseminates a new life style. This changes is determinant in the formation process of the young people chooses.